Determination of the sanitary quality of unpasteurized fresh cheeses for human consumption in Sinaloa, Mexico. - Reyes Tapia, Héctor (2023)
Fresh cheese represents a staple food of great importance for some communities, as well as an income from its commercialization; however, in some cases, the way it is processed could represent a risk to human health. Therefore, the objective of this study was to determine the sanitary quality of unpasteurized fresh cheeses intended for human consumption in Sinaloa. A total of 15, 20, 10, and 15 cheese samples were taken from Mazatlán, Culiacán, Guasave, and Los Mochis in the state of Sinaloa, México, respectively. The microbiological analysis was performed based on the Official Mexican Standard NOM-210-SSA1-2014. In accordance with the standard, the content of Escherichia coli, Staphylococcus aureus and Salmonella spp. was estimated. Of the total samples analyzed, 97% showed Escherichia coli, 57% S. aureus, and 13% Salmonella spp., above the reference values. The presence of indicator microorganisms and pathogens represents a risk factor for acquiring foodborne diseases, and also makes evident the need to improve hygienic practices in the preparation and preservation of these products.